Humoristes cherchent « safe spaces » - Blais-Poulin, Charles-Éric (La Presse, 2022)
Harcèlement en ligne, blagues sexistes, sous-représentation féminine, culture du silence : des humoristes n’entendent plus à rire. Elles sont « fucking tannées », « exténuées », « fâchées ». Et certaines aménagent leurs propres « safe spaces » (espaces sûrs), si de tels lieux existent.
Keywords: 2000 à aujourd'hui; 2010-2019; 2020-2029; LGBTQIA2+; amériques; approches et analyses; dénonciations en ligne; identités LGBTQIA2+; patriarcat; périodes historiques; québec; ressource en ligne; régions géographiques; safe space; sororité; systèmes d'oppressions; thématiques; travail; violences; violences sexistes et sexuelles

Dude, you're a fag: masculinity and sexuality in high school : with a new preface - Pascoe, C. J. (University of California Press, 2012)
"High school and the difficult terrain of sexuality and gender identity are brilliantly explored in this smart, incisive ethnography. Based on eighteen months of fieldwork in a racially diverse working-class high school, Dude, You're a Fag sheds new light on masculinity both as a field of meaning and as a set of social practices. C.J. Pascoe's unorthodox approach analyzes masculinity as not only a gendered process but also a sexual one. She demonstrates how the 'specter of the fag' becomes a disciplinary mechanism for regulating heterosexual as well as homosexual boys and how the 'fag discourse' is as much tied to gender as it is to sexuality"–Provided by publisher.
Keywords: 2000 à aujourd'hui; 2000-2009; 2010-2019; LGBTQIA2+; adolescents*; amériques; approches et analyses; californie; cours; discipline; ethnographie; hétérosexisme; masculinité; patriarcat; premier cycle; périodes historiques; régions géographiques; sciences humaines; sexisme; soc2014; sociologie; systèmes d'oppressions; thématiques; états-unis